2016
DOI: 10.1136/jmedgenet-2016-103902
|View full text |Cite
|
Sign up to set email alerts
|

New paradigms forBRCA1/BRCA2testing in women with ovarian cancer: results of the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) study

Abstract: BackgroundOver recent years genetic testing for germline mutations in BRCA1/BRCA2 has become more readily available because of technological advances and reducing costs.ObjectiveTo explore the feasibility and acceptability of offering genetic testing to all women recently diagnosed with epithelial ovarian cancer (EOC).MethodsBetween 1 July 2013 and 30 June 2015 women newly diagnosed with EOC were recruited through six sites in East Anglia, UK into the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
77
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 27 publications
8
77
2
1
Order By: Relevance
“…The oldest mutation carrier identified was 84 years old. Our data contrast with a recent study from the east of England, where only one of 86 women over the age of 70 years carried a pathogenic mutation, which led the authors to conclude that testing should be restricted to patients under 70 years of age in the absence of positive family history. Our results are more in line with those of Norquist et al, who identified BRCA1/2 mutations in over 5% of their population aged 70–79 years .…”
Section: Discussioncontrasting
confidence: 99%
“…The oldest mutation carrier identified was 84 years old. Our data contrast with a recent study from the east of England, where only one of 86 women over the age of 70 years carried a pathogenic mutation, which led the authors to conclude that testing should be restricted to patients under 70 years of age in the absence of positive family history. Our results are more in line with those of Norquist et al, who identified BRCA1/2 mutations in over 5% of their population aged 70–79 years .…”
Section: Discussioncontrasting
confidence: 99%
“…There was a good validation of the new MSS (MSS3) in a population-based cohort of epithelial ovarian cancer22 with 15/17 (88.2%) being detected at the 10% (15-point) threshold.…”
Section: Discussionmentioning
confidence: 97%
“…In an East of England series (GTEOC study), the prevalence of germline pathogenic BRCA1/2 variants among all high-grade serous and endometrioid ovarian cancer cases was 8% (18/232) and increased to 12% (17/146) in women diagnosed under the age of 70 years, but fell to 1% (1/86) in those aged ≥70 years 19. Similarly, in a Scottish series, the prevalence of pathogenic BRCA1/2 variants among unselected non-mucinous epithelial ovarian cancer was 13.1% (31/236), but fell to 8.2% (13/159) in women diagnosed over the age of >70 years 20.…”
Section: Discussionmentioning
confidence: 99%